Un Dieu sadique : le rôle de l’image blasphématoire de Dieu dans Dolce agonia de Nancy Huston - Front, Izabela (Quêtes littéraires, 2013)
The present article seeks to analyze the way in which the blasphemous figure of God in Dolce agonia by Nancy Huston allows the author to describe the sacred element in human life, seen as deprived of transcendental character. This is possible thanks to the three aspects of the text dependent on the type of God’s figure, which are: the contrast between passages marked by the cynical God’s voice and passages focused on man’s life filled with suffering; the tone and the appropriation of time var-iations and, finally, the double character of God who, at the same time, is indifferent to man’s lot while touched by his capacity of love.